A Simulation Study for Trimetallic Nanosized Alloy (Ni, Cu, and Ag) in Hydrogenation of Organic Compounds: A Case Study of "Nitrophenols". (13th March 2017) - Bawaked, Salem M.; Abd El Maksod, Islam Hamdy; Alshehri, Abdulmohsen
Abstract : Trimetallic system (Ni, Cu, and Ag) supported on alumina was utilized for hydrogenation of nitrophenols. The catalytic active centers for hydrogenation were attributed only to the presence of Ni. However, the presence of bi- or trimetallic systems improves the catalytic activity via extra synergism. The catalytic activity was measured as the time for reaching 100% conversion. The function of synergism was fitted for both bimetallic systems (Ni:Ag; Ni:Cu) individually. Subsequently, three-dimensional function was fitted for trimetallic system (Ni:Cu:Ag) based on the linear combination of data for individual bimetallic system. After a complex calculation areal function was evaluated. An Excel program was written to simply evaluate the catalytic activity of trimetallic system with high accuracy. Characterization of catalysts was performed using EPR and pulsed chemisorption by hydrogen. These characterizations of samples enable us to evaluate particle size, metallic surface area, and degree of dispersion. These values were successfully correlated with the synergism function. The program written then could be capable of predicting these values for any trimetallic system.